Evaluation Of Development Of Museum History Of Jakarta As A Historical Attraction - Adrianus Waranei Muntu (Program Studi Hospitality dan Pariwisata, 2018)
AbstractThis article analyzes the evaluation of the Jakarta History Museum from a tourism perspective. The Jakarta History Museum, also known as the Fatahillah Museum, is one of the oldest buildings in Indonesia that was built in the era of Dutch colonialism. This study uses a qualitative descriptive approach that describes the circumstances and phenomena systematically as well as the characteristics of objects that are examined precisely based on the facts that actually happened. The contents of the discussion of this article describe in accordance with the 4A Theory of Tourism: attraction, accessibilities, amenities, ancillaries. This article is expected to contribute to the development of sustainable tourist attraction in Jakarta in general, and the Jakarta’s Old Town in particular. Keywords: Jakarta Historical Museum, Jakarta’s Old Town, Evaluation, History, Tourism, Tourist Attractions Abstrak